La spermatogenèse, l'ovogenèse, la fécondation et les premiers stades de développement chez Octavella galangaui - Tuzet, O.; Paris, J. (Vie & Milieu, 1964)
In this work, it has been observed spermatogenesis, ovogenesis, fecundation and first stages development of the calcareous Sponge Octavella Galangaui. Male specimens are much more numerous than females. The spermatogonia come from the change in-situ of the collar cells of a flagellated chamber. The spermatic follicules are many and there is formation of a lot of spermatozoïds. We have observed one ovogonies generation only. After its great growth, the ovocyte I goes through two mitoses of maturation. The fecundation is done through a collar cell in which the spermatozoïd enters and changes itself into a carrying cell. The spermatozo'id goes in the ovocyte at the beginning of the great growth; the carrying cell is absorbeb by the ovocyte. The ovocyte is surrounded by a placental membrane. The abondant vitellus is formed without any phagocyted cells. The segmentation at first is complete and equal. It gives an important morula in which two types of cells are present, one counting but a very few elements. The blastula occurs by a round order of cells which leaves empty the blastula cavity. This blastula is finally an amphiblastula with numerous high and narrow flagella cells and gathered in a pole a few larger rounded cells without flagella.